2011
DOI: 10.3168/jds.2010-3694
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters for milk somatic cell score and relationship with production and udder type traits in dairy Alpine and Saanen primiparous goats

Abstract: Goat milk somatic cell counts have been collected for several years in France by the national milk recording organization. Information is used for health management, because repeatedly elevated somatic cell counts are a good indirect predictor of intramammary infection. Genetic parameters were estimated for 67,882 and 49,709 primiparous goats of the dairy Alpine and Saanen breeds, respectively, with complete information for milk somatic cell counts and milk production traits. About 40% of the goats had additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

34
81
10
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(133 citation statements)
references
References 28 publications
34
81
10
8
Order By: Relevance
“…Genetic parameters for SCC estimated in the French Saanen, Alpine and New Zealand dairy goat populations (mostly Saanen) were slightly lower than those obtained in our study (0.20 -0.24 - Morris et al, 2011;Rupp et al, 2011). However, repeatability estimated by Morris et al (2011) was almost the same as obtained in our study (0.57 vs 0.55).…”
Section: Resultscontrasting
confidence: 53%
See 4 more Smart Citations
“…Genetic parameters for SCC estimated in the French Saanen, Alpine and New Zealand dairy goat populations (mostly Saanen) were slightly lower than those obtained in our study (0.20 -0.24 - Morris et al, 2011;Rupp et al, 2011). However, repeatability estimated by Morris et al (2011) was almost the same as obtained in our study (0.57 vs 0.55).…”
Section: Resultscontrasting
confidence: 53%
“…Another New Zealand study on mixed-breed dairy goats (Saanen, Nubian, Alpine and Toggenburg) revealed that heritability of SCS is lactation stage dependent, and increased from 0.12 to 0.25 from the beginning to the end of lactation, while repeatability ranged between 0.46 and 0.59 (Apodaca-Sarabia et al, 2009). The value obtained in our study, higher than in the French population (Rupp et al, 2011), might have been the result of involving different animal populations and using different models. Heritability for SCC was also estimated in Kenya by Bett et al (2012), however their estimates were much lower Table 1; ABC, ab means with different superscripts are significantly different at P < 0.01 and P < 0.05, respectively (0.15) than those previously mentioned and could be explained by the specific system of husbandry (low input smallholder systems in Kenya vs intensive systems in France, New Zealand or Poland).…”
Section: Resultscontrasting
confidence: 41%
See 3 more Smart Citations